Antiviral and anti-inflammatory evaluation of herbal extracts: Implications for the management of calf diarrheal diseases - Xi-Rui Xiang; Eun-Seo Lee; Junho Lee; Su Min Kyung; Han Sang Yoo (PLoS ONE, 2026)
Traditional herbal extracts are attracting attention in the context of animal disease control because of their low side effects, diverse bioactive compounds, and low antimicrobial resistance risk. However, the underlying mechanisms remain inadequately understood. To characterize the multifaceted biological activities that underlie their therapeutic potential, this study systematically evaluated the antiviral and complex immunomodulatory properties of three distinct herbal combinations (designated Extracts A, B, and C) in vitro . The antiviral activities of the extracts were tested against bovine rotavirus and bovine coronavirus, two major pathogens of neonatal calf diarrhea, and their regulation of inflammatory mediators was assessed in a murine macrophage model (RAW 264.7 cells) stimulated with lipopolysaccharide from Escherichia coli by measuring nitric oxide production and the gene expression of inflammation related enzymes. Immunomodulatory effects were investigated by analyzing the gene expression of T helper cell-associated cytokines in both RAW 264.7 cells and bovine peripheral blood mononuclear cells (PBMCs). All three extracts exhibited inhibitory activity against both viruses and reduced the expression of specific inflammatory mediators. Furthermore, the extracts demonstrated complex immunomodulatory effects in bovine PBMCs, with Extract C promoting T helper 1 and T helper 17 responses while suppressing the regulatory T-cell transcription factor Forkhead Box P3. In conclusion, this in vitro study demonstrates that these herbal extracts possess antiviral and immunomodulatory potential, providing a basis for future studies to determine their relevance in viral infections associated with calf diarrhea.